Persepsi Mahasiswa Akuntansi Terhadap Faktor-Faktor Yang Mendorong Pemilihan Profesi Akuntan Publik - Margareta Yopeng; Aprina Nugrahesthy Sulistya Hapsari (Tirtayasa Ekonomika, 2020)
This study aims to determine the factors that encourage students' interest to choose the profession as a public accountant in terms of financial rewards (salary), work environment, professional training, professional recognition and herding. The research expected to provide an overview of the factors that encourage a person to choose the profession as a public accountant. This research uses a qualitative descriptive that using descriptive analysis method through primary data in the form of a questionnaire distributed directly to the respondents. The population in this study are Accounting active student class of 2016, that use sample size of 80 respondents and calculated using the Slovin. The results indicate that financial rewards (salary), work environment, professional training, professional recognition and herding are the driving factors in choosing the public accounting as a profession.